Spetzler-Martin grade I and II cerebral arteriovenous malformations: a propensity-score matched analysis of resection and stereotactic radiosurgery in adult patients - Tos, Salem; Osama, Mahmoud; Mantziaris, Georgios; Hajikarimloo, Bardia; Adeeb, Nimer; Kandregula, Sandeep; Dmytriw, Adam A.; Salim, Hamza Adel; Musmar, Basel; Naamani, Kareem El; Ogilvy, Christopher; Kondziolka, Douglas; et al. (Neurosurgical review, 2025)
Cerebral arteriovenous malformations (AVMs) are congenital vascular anomalies that can lead to severe complications, including hemorrhage and neurological deficits. This study compares the outcomes of microsurgical resection and stereotactic radiosurgery (SRS) for SM grade I and II AVMs. Out of a large multicenter registry, we identified 180 matched patients with SM grade I and II AVMs treated with either microsurgical resection or SRS between 2010 and 2023. The primary outcomes were AVM obliteration rates and complications; secondary outcomes included neurological status and functional outcomes measured by the modified Rankin Scale (mRS). Propensity score matching (PSM) was utilized to ensure comparability between treatment groups. After PSM, 90 patients were allocated to each treatment group. Significant differences were observed in complete obliteration rates, with resection achieving higher rates compared to SRS in overall cases (97.8% vs. 60.0%, p < 0.001), unruptured AVMs (100% vs. 58.3%, p < 0.001), and ruptured AVMs (95.2% vs. 61.9%, p < 0.001). Functional improvement rates were similar between the groups for overall cases (67.2% in resection vs. 66.7% in SRS, p = 0.95), unruptured AVMs (55.2% in resection vs. 55.6% in SRS, p > 0.9), and ruptured AVMs (78.1% in resection vs. 74.1% in SRS, p = 0.7). Symptomatic complication rates were identical between the groups (11.1% each, p > 0.9), while permanent complication rates were comparable (6.7% in resection vs. 5.6% in SRS, p = 0.8). Resection demonstrated significantly higher complete obliteration rates compared to SRS across all cases, including unruptured and ruptured AVMs. Functional improvement rates were similar between the two treatment groups, with no significant differences in symptomatic or permanent complication rates.
Gesehen am 15.09.2025